Fluid flow and heat transfer of natural convection around heated V-shaped cavity - Fumiyoshi KIMURA (The Japan Society of Mechanical Engineers, 2016)
Natural convective flows around V-shaped cavities are encountered in some engineering applications such as over the heat-transfer plates or roofs having triangular-shaped grooves. In order to assess the heat transfer performance of these plates or roofs, detailed information on their flow and heat transfer will be needed. Thus, the experimental investigations have been carried out on natural convection of water induced around a heated, V-shaped open cavity. The open angles, θ, and the side lengths, W / 2, were varied systematically as θ = 90-180° and W / 2 = 25, 50, 100 mm. The flows in the cavity and the surface temperatures were visualized with fine nylon particles and a thermo-chromic liquid crystal sheet, respectively. The results showed that the ambient fluid first descends to the bottom edge of the cavity, and, then, directs to the upper edge of cavity when θ<135°. The local heat transfer coefficients were also measured. The results showed that the heat transfer is enhanced markedly when θ =120°. It is also found that the overall heat transfer coefficients from the cavity θ = 120° and W / 2 = 25 mm became 17% higher than that from the horizontal plate.